Yehuda Jean-Bernard Moraly. L’Œuvre impossible: Claudel, Genet, Fellini. Paris: Éditions le Manuscrit, 2013. 207 pp. - Eric Touya de Marenne (Studies in 20th & 21st Century Literature, 2015)
Review of Yehuda Jean-Bernard Moraly. L’Œuvre impossible: Claudel, Genet, Fellini. Paris: Éditions le Manuscrit, 2013. 207 pp.
Keywords: unfinished works; creative process; Paul Claudel; Jean Genet; Federico Fellini